2009
DOI: 10.1002/pds.1870
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin use and cancer risk: a meta‐analysis of individual patient data from long‐term prospective controlled trials in Japan

Abstract: Pravastatin did not increase the rate of cancer incidence or cancer death in a large population of Japanese patients followed for >70,000 patient-years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 35 publications
2
36
1
Order By: Relevance
“…We found an association between statin use and reduced risk of certain B‐cell NHL subtypes (DLBCL and PCN). These findings are consistent with results from other studies . We previously reported a similar reduction of overall NHL risk associated with ever‐use of statins in a meta‐analysis of these studies .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found an association between statin use and reduced risk of certain B‐cell NHL subtypes (DLBCL and PCN). These findings are consistent with results from other studies . We previously reported a similar reduction of overall NHL risk associated with ever‐use of statins in a meta‐analysis of these studies .…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with results from other studies. [8][9][10][11][32][33][34] We previously reported a similar reduction of overall NHL risk associated with ever-use of statins in a meta-analysis of these studies. 15 Another study published later verified the inverse association between NHL risk and statin use (OR 5 0.52, 0.43-0.62).…”
Section: Discussionmentioning
confidence: 92%
“…Sato et al (21) reported an observed/expected ratio of 0.63 (95%CI=0.01–3.49) in a pravastatin trial that included 179 participants in the statins arm, one of whom developed liver cancer. Matsushita et al (20), in a meta-analysis of three Japanese studies of pravastatin, reported a hazard ratio of 0.58 (0.18–1.84) based on 7 liver cancers in the control group and 5 liver cancers in the pravastatin group. Similarly, in a large meta-analysis of cancer outcomes in 27 trials (19), no relationship between statin use and liver cancer was identified (p=0.39), with 42 liver cancers reported in the statins arm and 51 in the control arm.…”
Section: Discussionmentioning
confidence: 99%
“…33 The remaining meta-analyses reported null associations between statin use and breast cancer risk, even when stratified by statin type and study design. 6,2932 …”
Section: Statins and Breast Cancer Preventionmentioning
confidence: 99%